2006
DOI: 10.1103/physrevb.74.245417
|View full text |Cite
|
Sign up to set email alerts
|

Band-gap unification of partially Si-substituted single-wall carbon nanotubes

Abstract: The atomic and electronic structure of a set of pristine single wall SiC nanotubes as well as Si-substituted carbon nanotubes and a SiC sheet was studied by the local-density approximation ͑LDA͒ plane wave band structure calculations. Consecutive substitution of carbon atoms by Si leads to a gap opening in the energetic spectrum of the metallic ͑8,8͒ SWCNT with approximately quadratic dependence of the band gap upon the Si concentration. The same substitution for the semiconductor ͑10,0͒ single wall carbon nan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 70 publications
(129 reference statements)
0
6
0
Order By: Relevance
“…Unlike CNTs, the band structure of BNNTs shows semiconducting properties with a nearly constant band gap (5.5 eV), which is weakly dependent on the tube diameter and chirality. Therefore, the modification of their properties by doping has attracted a great deal of interest. Recent work has revealed that the band gap of BNNTs can be effectively tailored by carbon (C) doping, depending on their atomic compositions and configurations. On the other hand, the doping of silicon (Si), which belongs to the same group as C, group IV, but strongly prefers sp 3 -like bonding, is considered to influence the electronic and structural properties of CNTs and BNNTs in a different way from that of C doping. Theoretically, it was predicted that the large outward displacement of the Si atom and its nearest-neighbor C atoms may impose changes in the chemical reactivity and, hence, in the interaction with foreign atoms and molecules through the Si sites. , A quadratic dependence of the band gap upon the Si concentration was also calculated for single-walled CNTs . Unfortunately, no experimental reports of Si-doped CNTs have so far been published, which would allow the theoretical predictions to be confirmed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike CNTs, the band structure of BNNTs shows semiconducting properties with a nearly constant band gap (5.5 eV), which is weakly dependent on the tube diameter and chirality. Therefore, the modification of their properties by doping has attracted a great deal of interest. Recent work has revealed that the band gap of BNNTs can be effectively tailored by carbon (C) doping, depending on their atomic compositions and configurations. On the other hand, the doping of silicon (Si), which belongs to the same group as C, group IV, but strongly prefers sp 3 -like bonding, is considered to influence the electronic and structural properties of CNTs and BNNTs in a different way from that of C doping. Theoretically, it was predicted that the large outward displacement of the Si atom and its nearest-neighbor C atoms may impose changes in the chemical reactivity and, hence, in the interaction with foreign atoms and molecules through the Si sites. , A quadratic dependence of the band gap upon the Si concentration was also calculated for single-walled CNTs . Unfortunately, no experimental reports of Si-doped CNTs have so far been published, which would allow the theoretical predictions to be confirmed.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13] On the other hand, the doping of silicon (Si), which belongs to the same group as C, group IV, but strongly prefers sp 3 -like bonding, is considered to influence the electronic and structural properties of CNTs and BNNTs in a different way from that of C doping. [14][15][16][17][18][19][20] Theoretically, it was predicted that the large outward displacement of the Si atom and its nearest-neighbor C atoms may impose changes in the chemical reactivity and, hence, in the interaction with foreign atoms and molecules through the Si sites. 14,15 A quadratic dependence of the band gap upon the Si concentration was also calculated for singlewalled CNTs.…”
Section: Introductionmentioning
confidence: 99%
“…The doping of silicon (Si), which belongs to the same group as C, is also studied for carbon nanotubes (CNTs) [45] and boron nitride nanotubes (BNNTs) [46]. In the present work, Si and phosphorus (P) substituted h-BN sheets were considered using density functional theory (DFT) in order to assess the influence of Si and P dopants on the structural and energetics properties at the B and N sites.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental measurements based on Cathodoluminescence method have estimated values from 5.3 to 5.4 eV [19,20]. Studying the effects of group IV elements on the electronic properties of BNNT's is an attractive subject that many workers have reported many of the structural and electronic properties for C, Si and Ge-doped BNNT in recent years [21][22][23][24][25][26][27][28][29][30][31][32]. However there are not any researches considering the effects of Sn and Pb.…”
Section: Introductionmentioning
confidence: 99%